2009
DOI: 10.4329/wjr.v1.i1.3
|View full text |Cite
|
Sign up to set email alerts
|

Incremental value of magnetic resonance imaging in the advanced management of prostate cancer

Abstract: Prostate cancer is a major public health burden throughout the world. The high incidence of prostate cancer, combined with earlier detection and downstaging at the time of diagnosis, and the slow natural progression and biological heterogeneity of the disease, has made its management a complex and controversial issue. There is growing demand for patient-specific therapies that can minimize treatment morbidity while maximizing treatment benefits. There are a number of clinical parameters and clinical nomograms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 109 publications
0
8
0
Order By: Relevance
“…Radical prostatectomy in organ defined prostate cancer seems to have excellent prognosis, as more than 90% (ref. 2 ) are free from recurrence at 5 years. Nomogram prediction of organ defined prostate cancer is high with under the receiver operating characteristic (ROC) curve ranging from 0.79 to 0.82.…”
Section: Tumor Localisationmentioning
confidence: 99%
See 4 more Smart Citations
“…Radical prostatectomy in organ defined prostate cancer seems to have excellent prognosis, as more than 90% (ref. 2 ) are free from recurrence at 5 years. Nomogram prediction of organ defined prostate cancer is high with under the receiver operating characteristic (ROC) curve ranging from 0.79 to 0.82.…”
Section: Tumor Localisationmentioning
confidence: 99%
“…2 ) and sensitivity 46-96% (ref. 2 ). A prospective study of 27 patients reported that MRI had significantly higher standardized canonical discriminant function coefficient than Partin tables in predicting extracapsular extension of PC (ref.…”
Section: Tumor Localisationmentioning
confidence: 99%
See 3 more Smart Citations